Effect of low-level laser therapy in the treatment of oral mucositis in patients with head and neck cancer: a scoping review (Arquivos em Odontologia, 2024)
Aim: This article aims to evaluate, using the best sources of evidence, the contribution of low-level lasers in treating oral mucositis in patients with oral cancer.Methods: This review, including the entire process of the selection of studies and preparation of results, complied with the PRISMA-ScR protocol guidelines. At the end of the predefined analyses (title, abstract, and full text), 02 studies were included that correctly fit the eligibility criteria. These were published in 2015 and 2019 and were classified according to level II of the Agency for Healthcare of Research and Quality (AHRG). After critically reading the study, the common topics addressed in this scoping review were defined.Results: Two works brought considerations about the laser therapy protocol, the use of the visible red wavelength, and energy densities between 3 and 4 J/cm². In addition, positive correlations were identified between painful symptoms and nutritional status with oral mucositis, as low-level laser therapy reduced pain and weight loss and improved the nutritional quality of cancer patients.Conclusion: Photobiomodulation proved effective in treating mucositis at higher degrees. Scientific evidence on this topic is still being developed, but it will be promising and valid if more research is conducted.